2017
DOI: 10.1038/s41598-017-03866-8
|View full text |Cite
|
Sign up to set email alerts
|

Small head size and delayed body weight growth in wild Japanese monkey fetuses after the Fukushima Daiichi nuclear disaster

Abstract: To evaluate the biological effect of the Fukushima Daiichi nuclear disaster, relative differences in the growth of wild Japanese monkeys (Macaca fuscata) were measured before and after the disaster of 2011 in Fukushima City, which is approximately 70 km from the nuclear power plant, by performing external measurements on fetuses collected from 2008 to 2016. Comparing the relative growth of 31 fetuses conceived prior to the disaster and 31 fetuses conceived after the disaster in terms of body weight and head si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 23 publications
4
38
0
Order By: Relevance
“…In addition, data from non-human primatesthe closest taxonomic relatives to humans-should make Open Access BMC Research Notes *Correspondence: toshinoriomi@gmail.com 1 Nippon Veterinary and Life Science University, 1-7-1 Kyonancho, Musashino City, Tokyo 180-8602, Japan Full list of author information is available at the end of the article a notable contribution to future research examining the health effects of radiation exposure in humans. In our previous study, we detected high levels of radiocaesium in muscle [10] and reported haematologic effects [11] as well as changes in head size and delayed body weight gain in wild Japanese monkeys [12] after the FDNPP disaster. In the present study, we determined the distribution of 137 Cs in various organs and tissues of wild Japanese monkeys inhabiting the forested areas surrounding Fukushima City that were captured between July and August 2012.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In addition, data from non-human primatesthe closest taxonomic relatives to humans-should make Open Access BMC Research Notes *Correspondence: toshinoriomi@gmail.com 1 Nippon Veterinary and Life Science University, 1-7-1 Kyonancho, Musashino City, Tokyo 180-8602, Japan Full list of author information is available at the end of the article a notable contribution to future research examining the health effects of radiation exposure in humans. In our previous study, we detected high levels of radiocaesium in muscle [10] and reported haematologic effects [11] as well as changes in head size and delayed body weight gain in wild Japanese monkeys [12] after the FDNPP disaster. In the present study, we determined the distribution of 137 Cs in various organs and tissues of wild Japanese monkeys inhabiting the forested areas surrounding Fukushima City that were captured between July and August 2012.…”
Section: Introductionmentioning
confidence: 89%
“…Samples of muscle, brain, heart, kidney, liver, lung, and spleen were collected from 10 Japanese monkeys (Macaca fuscata) captured between July and August 2012 from the forested areas around Fukushima City. These monkeys were used in a previously reported study to determine the concentrations of 134 Cs and 137 Cs in the muscles and characterize the changes in concentration over time as well as their relationship with soil contamination levels [12]. Organ and tissue samples were stored frozen at − 30 °C after 2012 until they were used in the present study.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, morphological and other abnormalities in butterflies (Hiyama et al, 2012(Hiyama et al, , 2015, DNA damage in cattle (Nakamura et al, 2017) and in mice (Kawagoshi et al, 2017;Kubota et al, 2015), changes in reproductive or developmental functions in mice (Takino et al, 2017) and monkeys (Hayama et al, 2017), as well as decreased blood cell counts in monkeys (Ochiai et al, 2014) and carp (Suzuki, 2015) were reported. For example, morphological and other abnormalities in butterflies (Hiyama et al, 2012(Hiyama et al, , 2015, DNA damage in cattle (Nakamura et al, 2017) and in mice (Kawagoshi et al, 2017;Kubota et al, 2015), changes in reproductive or developmental functions in mice (Takino et al, 2017) and monkeys (Hayama et al, 2017), as well as decreased blood cell counts in monkeys (Ochiai et al, 2014) and carp (Suzuki, 2015) were reported.…”
mentioning
confidence: 99%
“…Suspicious effects of radiation exposure on wildlife have also been reported in the contaminated area. For example, morphological and other abnormalities in butterflies (Hiyama et al, 2012(Hiyama et al, , 2015, DNA damage in cattle (Nakamura et al, 2017) and in mice (Kawagoshi et al, 2017;Kubota et al, 2015), changes in reproductive or developmental functions in mice (Takino et al, 2017) and monkeys (Hayama et al, 2017), as well as decreased blood cell counts in monkeys (Ochiai et al, 2014) and carp (Suzuki, 2015) were reported. Such reports may exacerbate the anxiety of residents, so further studies are required to clarify the effects of radioactive contamination by the Fukushima nuclear accident.…”
mentioning
confidence: 99%